2023
DOI: 10.1161/circulationaha.122.062885
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Cardiac Myosin Light Chain Kinase Ameliorates Systolic Dysfunction by Reducing Superrelaxed Myosin

Abstract: Background: Cardiac-specific myosin light chain kinase (cMLCK), encoded by MYLK3 , regulates cardiac contractility through phosphorylation of ventricular myosin regulatory light chain. However, the pathophysiological and therapeutic implications of cMLCK in human heart failure remain unclear. We aimed to investigate whether cMLCK dysregulation causes cardiac dysfunction and whether the restoration of cMLCK could be a novel myotropic therapy for systolic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…We read with great interest the article by Hitsumoto et al showing that cardiac myosin light chain kinase (cMLCK) knock-in mice and cells with the human dilated cardiomyopathy gene mutation developed systolic dysfunction and could be rescued by CRISPR-mediated gene correction and adenoviral vector expression of cMLCK. 1 They used C57BL/6N mice to develop cMLCK knock-in mice. However, we and another group independently discovered that C57BL/6N mice are a natural strain with cMLCK( MYLK3 ) deficiency due to a point mutation that produces an out-of-frame start codon 5 nucleotides upstream from a normal codon compared with C57BL/6J mice.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article by Hitsumoto et al showing that cardiac myosin light chain kinase (cMLCK) knock-in mice and cells with the human dilated cardiomyopathy gene mutation developed systolic dysfunction and could be rescued by CRISPR-mediated gene correction and adenoviral vector expression of cMLCK. 1 They used C57BL/6N mice to develop cMLCK knock-in mice. However, we and another group independently discovered that C57BL/6N mice are a natural strain with cMLCK( MYLK3 ) deficiency due to a point mutation that produces an out-of-frame start codon 5 nucleotides upstream from a normal codon compared with C57BL/6J mice.…”
Section: To the Editormentioning
confidence: 99%
“…The fact that the cMLCK mutant can cause dilated cardiomyopathy both in humans 4 and rodents in their natural courses 1,3 indicates that the regulation of the MLC phosphorylation level plays a very important role in the development of dilated cardiomyopathy and can be a crucial therapeutic target in the heart, as they proposed. 1 We would like to encourage every researcher to use C57BL/6J mice, and not C57BL/6N mice, when they study the regulation of MLC phosphorylation by the balance between cMLCK and MLC phosphatase signaling. 5…”
mentioning
confidence: 99%
“…We thank Okamoto et al for their thoughtful comments regarding our article. 1 They highlighted the importance of considering mouse strains in studying the regulation of myosin light chain phosphorylation via the balance between cMLCK (cardiac-specific myosin regulatory light chain kinase) and myosin regulatory light chain phosphatase signaling. 2 First, we apologize for the error in describing the method of creating knock-in (KI) mice models with a familial dilated cardiomyopathyassociated Mylk3 [myosin light chain kinse 3] frameshift (fs) mutation.…”
Section: Response To Letter To the Editormentioning
confidence: 99%
“…Indeed, wild-type (Mylk3 +/+ ) and heterozygous mice (MYLK3 +/fs ) express the wild-type cMLCK protein, consistent with the approximately 90-kDa band detected by the cMLCK antibody on western blotting. 1 In addition, the knock-in allele does not have an single nucleotide polymorphism located at nucleotide 146 of exon 1 of Mylk3, a T to A mutation that creates a new initiation codon and causes frameshift and elimination of cMLCK protein expression. 2 Therefore, we concluded that the systolic dysfunction observed in our knock-in mice was caused by cMLCK protein deficiency.…”
Section: Response To Letter To the Editormentioning
confidence: 99%
“…The myocardial contractile mechanisms involving cMLCK (cardiac-specific myosin light chain kinase) discovered by Hitsumoto et al 1 appear to be related to the major causes of human heart failure. Doxorubicin cardiomyopathy due to mitochondrial disorders, ischemic cardiomyopathy due to inflammation and fibrosis after myocardial ischemia, dilated and hypertrophic cardiomyopathy due to sarcomeric protein abnormalities, whatever the cause of contractile dysfunction, the authors found that the ratio of MYLK3/PPP1R12B mRNA was significantly decreased in the myocardium.…”
Section: To the Editormentioning
confidence: 99%